The effects of nanomaterials on blood coagulation in hemostasis and thrombosis. (11th January 2017) - Simak, Jan; De Paoli, Silvia
Abstract : The blood coagulation balance in the organism is achieved by the interaction of the blood platelets (PLTs) with the plasma coagulation system (PCS) and the vascular endothelial cells. In healthy organism, these systems prevent thrombosis and, in events of vascular damage, enable blood clotting to stop bleeding. The dysregulation of hemostasis may cause serious thrombotic and/or hemorrhagic pathologies. Numerous engineered nanomaterials are being investigated for biomedical purposes and are unavoidably exposed to the blood. Also, nanomaterials may access vascular system after occupational, environmental, or other types of exposure. Thus, it is essential to evaluate the effects of engineered nanomaterials on hemostasis. This review focuses on investigations of nanomaterial interactions with the blood components involved in blood coagulation: the PCS and PLTs. Particular emphases include the pathophysiology of effects of nanomaterials on the PCS, including the kallikrein‐kinin system, and on PLTs. Methods for investigating these interactions are briefly described, and a review of the most important studies on the interactions of nanomaterials with plasma coagulation and platelets is provided. WIREs Nanomed Nanobiotechnol 2017, 9:e1448. doi: 10.1002/wnan.1448 This article is categorized under: Implantable Materials and Surgical Technologies > Nanomaterials and Implants Toxicology and Regulatory Issues in Nanomedicine > Toxicology of Nanomaterials Abstract : Effects of nanomaterials on blood platelets and plasma coagulation system.